Motivation and pedagogy of non-music education graduates in music classes - Ebro, Carmelle Joyce F. (2009)
This study aimed to investigate and compare the music background, training, teaching experiences, and motivation ten grade 5 music teachers with non-degrees in music education. Survey questionnaires were used to obtain teacher profile, music teacher efficacy beliefs, and achievement goal orientation. Interviews of students and teachers were transcribed, coded, and clustered to form themes, then analyzed to form individual case study reports together with observation and field notes. Results showed that teachers have high music efficacy beliefs and higher mastery goal orientation than performance goal orientation. These factors affected their pedagogy positivley and complimented narratives and observation of the respondents. The teachers have been very resourceful in learning to teach music.